Electrostatic Ion Cyclotron Waves Observed by CSES in the Equatorial Plasma Bubble. Issue 4 (14th February 2023) - Gou, Xiaochen; Li, Lei; Zhou, Bin; Zhang, Yiteng; Xie, Lianghai; Cheng, Bingjun; Feng, Yongyong; Wang, Jindong; Miao, Yuanqing; Zhima, Zeren; Shen, Xuhui
Abstract: Broadband ELF electrostatic emissions have been observed by the China Seismo‐Electromagnetic Satellite (CSES) inside the equatorial plasma bubbles (EPBs). Analyses reveal that the electric field fluctuates nearly perpendicular to the ambient magnetic field, with the transverse component gyrotropically distributed around the magnetic field line. The observed emissions, Doppler shifted and broadened, are found to be close to the local oxygen ion (O + ) cyclotron frequency in the plasma reference frame. Accompanying ion heating and deceleration are consistent with the consequences of the ion cyclotron resonance. All these results indicate that the electrostatic emissions pervading a major part of the EPB are the O + electrostatic ion cyclotron (EIC) waves. The inhomogeneous‐energy‐density‐driven instability triggered by the non‐uniform electric field and density gradient across the EPBs could be the source of the EIC waves. The CSES observation provides new evidence for the shear driven EIC wave in the equatorial ionosphere. Plain Language Summary: The O + electrostatic ion cyclotron (EIC) wave is an electrostatic plasma wave mode with frequency related to the Oxygen ion cyclotron frequency. In the topside ionosphere, the O + EIC wave is difficult to identify since the waves observed by spacecrafts are Doppler shifted and broadened. The electrostatic fluctuations inside the equatorial plasma bubbles (EPBs) have usually been taken as Doppler shifted signals from the static charge structures. Based on full set of field and plasma measurements on board the China Seismo‐Electromagnetic Satellite (CSES), here we present a new observation about the EIC waves inside the EPBs. Through analyses, we reveal the properties of the electric field fluctuations, including their real frequencies, polarity and propagation directions, all are in excellent consistency with these of the O + EIC waves. Moreover, ion heating and deceleration observed inside the EPB agree well with the consequences of the EIC waves. Thus we judge that EIC waves do exist inside the EPB. The non‐uniform electric field and density gradient in EPBs could favor growth of the EIC waves. Our finding suggests that the EIC wave may play a role in the evolution of the equatorial ionospheric irregularities. Key Points: Oxygen ion electrostatic ion cyclotron (EIC) waves can develop inside the equatorial plasma bubble Ion cyclotron resonance is a mechanism for ion temperature enhancement inside the equatorial plasma bubble The inhomogeneous transverse electric field and density gradient in the equatorial plasma bubble could act as the source of the EIC waves